MRV of soil organic carbon: Where are we and what is missing? - Bernoux, Martial (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Presentation by Martial Bernoux, Natural Resources Officer for the Climate and Environment Division of the FAO, Rome. The presentation was part of the Webinar on Soil carbon in the Nationally Determined Contributions hosted by CCAFS, the German Ministry of Food and Agriculture, and the 4 Per Mille Initiative and held on Earth Day, 22 April 2020.